Physiological and psychological stress responses to labor and delivery during COVID-19 pandemic: a cohort study - Aula Asali; Sivan Farladansky-Gershnabel; Noa Hasky; Michal Elbaz; Ami Fishman; Dorit Ravid; Amir Wiser; Tal Biron-Shental; Arie Berkovitz; Netanella Miller (Taylor & Francis Group, 2022)
Objective To evaluate objective (saliva cortisol) and subjective (questionnaire) stress levels during the Coronavirus disease (COVID-19) pandemic compared to before the pandemic and their effects on obstetric and neonatal outcomes. Methods This cohort study included 36 women with low-risk, singleton, term deliveries at a tertiary academic center during the COVID-19 pandemic and 49 who delivered before. Physiological stress was evaluated with salivary cortisol measurements, and emotional stress with stress scale questionnaires (0-10) during active and full dilation stages of labor, and 2-min postpartum. Cord blood cortisol and pH were obtained. Delivery mode, complications, and neonatal outcomes were evaluated. Results Psychological stress was higher for the COVID-19 group compared to controls during full dilation (6.2 ± 3.4 vs. 4.2 ± 3, p = .009). The COVID-19 group had significantly lower cord cortisol levels (7.3 vs. 13.6 mcg/dl, p = .001). No differences were found regarding salivary cortisol level assessments at active, full dilation and 2-min post-delivery (p = .584, p = .254, p = .829, respectively). No differences were found regarding pH < 7.1 (p = .487), 1- and 5-min Apgar scores < 7 (p = .179) and neonatal weight (p = .958). Conclusions Women who delivered during COVID-19 pandemic had higher stress levels at full dilation and lower cord cortisol levels, as may be expected after exposure to a chronic stressor.